f(x)= 1/ (x-1)
By the definition f'(x) = lim[(f(x+dx) - f(x))/dx] as dx --> 0.
Heref(x+dx) - f(x) = 1/(x+dx-1) - 1/(x-1) = [(x-1) - (x+dx-1)]/[(x-1+dx)*(x-1)] = -dx/[(x-1+dx)*(x-1)].
Now / this by dx and obtain -1/[(x-1+dx)*(x-1)]. When dx --> 0, (x-1+dx) --> (x-1), so-1/[(x-1+dx)*(x-1)] --> -1/[(x-1)^2] (for any x except x=1, of course).
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?